Combined vs. single supplementation of l-citrulline and sodium bicarbonate during sprint interval training in basketball players: Effects on physical performance and hormonal adaptations - Wang, Y.; Wang, Y.; Qian, K. (Journal of Sports Science & Medicine, 2025)
This study examined the effects of L-citrulline (L-CIT) and sodium bicarbonate (Sb) supplementation during short sprint interval training (SSIT), both individually and combined, over a 28-day period, to assess the impact on the physical performance and hormonal adaptations of basketball players. Forty young (age = 21.5 ± 1.7 years) male basketball players were randomly assigned into five groups of eight subjects including either L-CIT (6 g daily), Sb (0.3 g·kg-1 of Sb daily), L-CIT+Sb, placebo (PL), and or an active control group (CON). The training groups engaged in SSIT sessions, consisting of three sets of ten repetitions of five-second all-out sprints, three times per week over four weeks. A series of physical performance tests including countermovement vertical jump, a 20-m linear sprint, Illinois change of direction speed, Wingate anaerobic power, and an incremental exercise test were conducted before and after the training period. In addition, blood samples were obtained to analyze resting testosterone and cortisol levels before and after the training period. Significant improvements in physical performance were observed across all training groups after the 4-week intervention (p < 0.05). Notably, the groups receiving supplements exhibited more pronounced improvements in the physical performance tests (p < 0.01) in comparison to the PL group, indicating superior adaptations. In addition, no significant (p > 0.05) changes were seen in testosterone, but the supplement groups showed lower cortisol levels than other groups following the 4-week intervention. There were no significant differences in physical performance adaptations among the supplement groups. The study reveals that short-term supplementation of L-citrulline and sodium bicarbonate in the capsule form effectively enhance physical performance of basketball players in comparison to a placebo.